Dinamika Positivisme Hukum dalam Perspektif Modernisme dan Postmodernisme - Hermawan, Randi; Koto, Muhammad Yusril; Lubis, Fauziah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
In this stud, the dynamics of legal positivism are explored through the perspective of modernism and postmodernism to understand changes in the concept of positive law over time. By analysing the evolution of legal views from these two paradigms, this research aims to identify transformations in the understanding of positive law over time. By paying attention to the influence of modernism which emphasizes rationality and legal certainty and postmodernism which highlights the diversity of interpretations on social contexts, this study will provide in-depth insight into the complexity of the dynamics of legal positivism in the contemporary context.